Hubungan Tingkat Pengetahuan, Sikap dan Perilaku Masyarakat Sulawesi Tenggara Terhadap Upaya Pencegahan dan Penyebaran Covid-19 - Wa Ode Masrida; Hesti Trisnianti Burhan; Nur Fitriana Muhammad Ali; Nugraha Dwi Akhir; Restu Nur Hasanah Haris (Jurnal Penelitian Sains dan Kesehatan Avicenna, 2022)
Background: Corona virus has become a global pandemic since 2019. The spread of this virus is so fast that it has taken thousands of lives. The incidence of Covid-19 in Indonesia until 2022 has reached 6.63 million and 160 thousand deaths. The Indonesian government is trying to prevent the spread of this virus by recommending complying with health protocols. This effort needs to be supported by knowledge, attitudes and behavior. Objective: to see the relationship between the level of knowledge and the attitudes and behavior of the people of Southeast Sulawesi towards efforts to prevent and spread Covid-19. Methods: The study used a cross-sectional design with data collection using an online questionnaire. The sample is the people of Southeast Sulawesi who meet the inclusion criteria. The total sample involved was 702 respondents. Data analysis used univariate and chi-square tests to see the relationship between the level of knowledge, attitudes and behavior of the community. Results: the level of knowledge of the people of Southeast Sulawesi regarding the prevention of Covid-19 is classified as poor (45.3%), attitudes shown are negative (50.7%) and bad behavior (54.0%). Conclusion: There is a relationship between the level of knowledge and the attitudes and behavior of the people of Southeast Sulawesi towards efforts to prevent and spread Covid-19.